TRiC controls transcription resumption after UV damage by regulating Cockayne syndrome protein A - Alex Pines (Nature Portfolio, 2018)
An integrated network of chaperones and protein degradation machineries called the proteostasis network (PN) is required to maintain protein homeostasis. Here the authors show that one of the components of the PN, the chaperonin TRiC, interacts with the core transcription-coupled nucleotide excision repair protein CSA to ensure its assembly into the CRLCSA complex.